Ring-by-ring femtosecond inscription of a multilayer single-mode Bragg grating in sapphire optical fiber - Wang, M; Salter, P; Payne, F; Shipley, A; Morris, S; Booth, M; Fells, J (Optica Publishing Group, 2022)
A multilayer Bragg grating was inscribed in sapphire optical fiber using a femtosecond laser. The grating was single-mode at 1550 nm with a ~0.3 nm bandwidth, showing potential for multi-point high-temperature sensing.